Sistema de inventario basado en tecnología de identificación por radiofrecuencia (RFID) en la carrera de Computación de la ESPAM MFL - López Mora, Christian Israel (2023)
The present curricular integration project aimed to develop an inventory system based on radio frequency identification (RFID) technology for managing technological equipment in the Computer Science program at ESPAM MFL. The Extreme Programming methodology was used for the development of this curricular integration project, which is based on four stages: Planning, Design, Development, and Testing. In the planning stage, all the necessary requirements were obtained to ensure the proper functioning of the system, and the communication architecture between the hardware and software was established. In the design stage, the corresponding class and use case diagrams were developed, and the communication architecture was visually designed. Subsequently, in the development stage, the backend and frontend were developed in ASP.NET, and the connection with the RFID reader was established. Finally, in the testing stage, the developed system was evaluated to validate its functionality. The implementation of an RFID-based inventory system has automated the management of technological equipment in the Computer Science program at ESPAM MFL. This solution has replaced manual administration, providing greater efficiency and accessibility to the data. Thanks to the web-based inventory system and the RFID reader, the data registration process has been streamlined, significantly reducing the required time.